The Effect of Exercise-Induced Central Fatigue on Cervical Spine Joint Position Error, Strength, and Endurance - Antonio Vintimilla; Troy Hooper; C. Roger James; Ho Cheng Lu; Karthick Natesan; Jeegisha Kapila; Phil Sizer (International Journal of Sports Physical Therapy)
# Background